Gambaran Dukungan Keluarga pada Peran Ibu Remaja di Kecamatan Sukowono-Jember - Qurrotul Ridho Khayun; Dini Kurniawati; Lantin Sulistyorini (Pustaka Kesehatan, 2021)
Adolescent mothers are a woman around 20 years old who is transitioning between children and adults but has to play a role as a parent. The transition period needs support from the closest family, husband, and closest person and hopefully can make it easier to be a mother to reduce their self-esteem or psychic in accepting the role of being a mother. The form of family support is instrumental support, informational support, support for self-esteem support from social groups. This study aimed to determine the description of family support in the role of adolescent mothers in the Sukowono Subdistrict, Jember Regency. This research used method explorative descriptive and total sampling method with 50 adolescent mothers as respondents. Data were analyzed by univariate analysis. This result showed that the respondents' characteristics mainly were 19 years old, all adolescent mothers worked as housewives (100%), and almost all of the monthly income was less than 1,000,000 (90%). A half of the respondents (50%) received family support from their husbands, parents, or in-laws in suitable categories. Therefore necessary family support is given to adolescent mothers to carry out their roles.